PENGARUH PENGGUNAAN COIL RACING KTC TERHADAP DAYA SEPEDA MOTOR 4 TAK TYPE YAMAHA ZUPITER Z1 113 CC TAHUN 2014 - Fikri Ulul Albab; Riki Irfan; Acep Awaludin (Jurnal Fakultas Teknik Kuningan, 2023)
In the automotive world, improving engine performance can be done by maximizing the performance of the ignition system in order to enlarge the sparks from the spark plugs so that the fuel and air mixture can burn perfectly. Complete combustion will cause the motor performance to increase. Therefore, the use of a racing coil as a device whose job is to strengthen the sparks on the spark plug is expected to increase power optimally. This study uses quantitative methods with experimental research. The standard coil transforms the 12 Volt battery voltage into a high voltage of more than 5000 Volts while the racing coil increases the high voltage to more than 10 Kilo Volts. The test results using the dynotest tool show that the lowest power produced by the standard coil is 0.0038 HP at 2000 rpm engine speed and the highest power generated is 0.0878 HP at 3500 rpm engine speed. While the lowest power generated by the racing coil is 0.0751 HP at 2000 rpm engine speed and the highest power generated is 0.1304 HP at 4000 rpm engine speed. Thus, it can be concluded that the use of coil racing on a motorcycle has a positive effect on the power generated. Where the power generated by using a racing coil is higher than the power generated by using a standard coil. There is a significant effect on the use of coil racing on the power of the yamaha zupiter Z1